Animal homes - Chessen, Betsey, 1970-; Chanko, Pamela, 1968- (New York : Scholastic, 1998)
Photographs and simple text describe the habitats of different animals.
"Scholastic early childhood"--P. [4] of cover.
Includes index.
Keywords: Animals -- Habitations -- Juvenile literature; Animals -- Habitations